TRAINING ON FINANCIAL STATEMENTS AND PRACTICE WITH THE DIGITAL-BASED 3N METHOD FOR CATFISH FARMING BUSINESS GROUPS IN BANTUL - Lestari, Septiana Ika; Wahyudi, Renaldi Dwi; Islamiati, Dian; Kurniawan, Irfan; Rinofah, Risal; Ogwu, Ibukun Yoyce (EMPOWERING HUMANITY, 2024)
This community service activity aims to help the Patil Berkah Jaya catfish farming group located in Gunturgeni village, Poncosari, Srandakan, Bantul. The problem that occurs in catfish farming groups is that financial reports are still compiled manually which is less efficient and error-prone. So that socialization and training on writing financial reports with a digital-based 3N (Niteni, Nirokke, Nambahi) strategy such as excel and google spreadsheets are needed. By conducting this training, it is hoped that it can provide knowledge and a positive impact on the understanding of writing financial reports digitally. As a result of this training, group members learned to make digital financial reports that are more efficient, accurate, and innovative, thus increasing transparency and facilitating financial evaluation for business development.